Adjustable compression wrap devices are cheaper and more effective than inelastic bandages for venous leg ulcer healing. A Multicentric Italian Randomized Clinical Experience. (March 2020) - Mosti, Giovanni; Mancini, Stefano; Bruni, Sergio; Serantoni, Simone; Gazzabin, Luca; Bucalossi, Matteo; Polignano, Roberto; Mariani, Fabrizio; Luca, Bastiani; Partsch, Hugo; ,
Introduction: Compression therapy by inelastic bandages is highly effective in achieving venous leg ulcer healing. Inelastic bandages may be expensive as they need to be changed and discarded at every dressing change. In addition, correct application is difficult in the clinical practice, even by expert healthcare personnel. The aim of our work was to assess whether adjustable compression wraps are more cost effective and more effective than inelastic bandage to achieve venous leg ulcer healing. Methods: Sixty-six venous leg ulcer patients were randomized to be treated by adjustable compression wrap (CircAid® JuxtaCure®) ( n  = 33) and inelastic bandage (Coban 2 Layer®) ( n  = 33). Study duration was 12 weeks. During weekly visits, the ulcers were cleansed and dressed with the same products, and the only variable was the compression device. Ulcer size, ulcer pain, patient's perception of compression systems, and compression pressure were assessed during the visits, and the material cost was evaluated at the 12th week. Results: Adjustable compression wraps were significantly cheaper than bandages (p < 0.0001) and were also more effective (not significantly) in achieving ulcer healing. To heal one ulcer patient, €228 had to be spent when applying an adjustable compression wrap and €381 if inelastic bandages were used. About 26/33 (78.8%) patients in the adjustable compression wrap group were healed after 12 weeks versus 23/33 (69.7%) in the inelastic bandage group (n.s.). Ulcer pain was reduced by both compression devices. Patient perception of compression pressure was similar with both compression devices. Compression pressure was similar at application but better maintained by adjustable compression wrap over time. Conclusions: Adjustable compression wraps are significantly cheaper and more effective (not significantly) in achieving venous leg ulcer healing. Self-applicable, adjustable compression wraps are therefore a powerful, cost-effective alternative to inelastic bandages in treating venous leg ulcer.